Regionális gazdasági fejlettségi különbségek a Kínai Népköztársaságban - Horváth, Gergely (Tér és Társadalom, 1988)
China's economy is full of distortions inherited from the pest, the abolition of which needs a well-considered strategy. These special inequalities can be seen in the regional location of the production forces and in the economic development of certain autonomous territories and lands. While after the proclamation of the people's republic in the period of the first five-year plans efforts to do away with the economy's decentralization and disparities were characteristic, being non-observant of its rentability. then, since the launching of the reform, development has been subject to profitability. The 7th five-year plan (1986-1990) goes hand in hand with the spirit of the economic reform, so far the greatest attention is given to the policy of regional economic development The present economic policy, which takes into account the realities in developing backward areas, will result, in the long term, decreasing disparities in the development.